Product variety and price strategy in the ski manufacturing industry - Nicoletta Corrocher; Marco Guerzoni (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2008)
The present paper aims at examining the role of variety in the ski manufacturing industry and its relevance in firms price setting strategies. In particular, it intends to investigate and empirically test two hypotheses concerning the relation between variety and prices. The first concerns the relationship between product quality/complexity and prices. The second refers to the existence of two kinds of varieties having opposite effects on price formation: market-related variety and production-related variety. We are able to empirically disentangle these two effects, by using variety in service characteristics as a proxy for market-related variety and variety in technical characteristics for production-related variety. Our empirical investigation confirms that prices are positively affected by product complexity and quality and positively affected by variety at the level of service characteristics. This means that a high degree of product variety allows firms to charge a premium price on consumers, who are able to find the product that best meet their needs and are therefore willing to pay a higher price. On the contrary, variety at the level of technical characteristics negatively impact on prices, because in a context where a dominant design emerges and new varieties are not radically different, gains in economies of scale and scope outweigh the cost of the increased flexibility in the equipment required to produce variety. The resulting decrease in marginal costs negatively impinges upon prices.
Keywords: L15; L23; O31; 330; variety; product and service characteristics; ski manufacturing sector; Wintersport; Sportartikelindustrie; Produktdifferenzierung; Produktqualität; Betriebliche Preispolitik; Europa